2017
DOI: 10.21325/jotags.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

The Food Waste in Five-Star Hotels: A Study on Turkish Guests Attitudes

Abstract: That nourishment is seen as an element of pleasure, taste and entertainment beyond a physiological need is causing food waste in hotel business. The food waste in hotels can be categorized into two main dimensions as the causes of business practices and the causes of consumer behavior, and this paper focuses on the latter. The main objective of this research is to determine the Turkish guests' food waste attitudes who are offered buffet service in five-star hotels. Additionally, this study has the sub-objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…The statements related to the environmental attitudes were negatively worded. Food-based food waste causes (seven items), ambiance-based food waste causes (six items), staff-based food waste causes (four items) and hygiene-based food waste causes (four items) were adapted from [47]. All the statements related to food waste causes were negatively worded.…”
Section: Instrumentsmentioning
confidence: 99%
“…The statements related to the environmental attitudes were negatively worded. Food-based food waste causes (seven items), ambiance-based food waste causes (six items), staff-based food waste causes (four items) and hygiene-based food waste causes (four items) were adapted from [47]. All the statements related to food waste causes were negatively worded.…”
Section: Instrumentsmentioning
confidence: 99%
“…In the catering and hotel sectors, both food-preparation workers and consumers are re-sponsible for losses. The waste of meals and food in places such as schools, kindergartens, canteens, gas stations, bars, restaurants, diners, and hotels is also problematic [12,13]. Such behavior is associated with significant economic and ecological losses.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the environmental impact of the hotel industry, a tional Hotels Environmental Initiative, on average, each guest waste per day [20], which doubles on check-out days [21]. Food nificant portion (more than one-third), with about 75% still being e Tekin and Ilyasov [23] confirmed that guests in all-inclusive hotel food and beverages than others because they will not pay for ext ver, all-inclusive hotels often serve their guests using an open buf of tackling food waste in all-inclusive resort hotels is a complic waste is frequently regarded as an unfortunate consequence of t Figure 1. Impacts of food waste in foodservice [13].…”
Section: Introductionmentioning
confidence: 99%
“…Food waste accounts for a significant portion (more than one-third), with about 75% still being edible [22]. Furthermore, Tekin and Ilyasov [23] confirmed that guests in all-inclusive hotel resorts often waste more food and beverages than others because they will not pay for extra consumption; moreover, all-inclusive hotels often serve their guests using an open buffet. Addressing the issue of tackling food waste in all-inclusive resort hotels is a complicated issue [24,25].…”
Section: Introductionmentioning
confidence: 99%